Adenoma, advanced adenoma and colorectal cancer prevalence in asymptomatic 40‐ to 49‐year‐old subjects with a first‐degree family history of colorectal cancer. (18th September 2013) - Del Vecchio Blanco, G.; Cretella, M.; Paoluzi, O. A.; Caruso, A.; Mannisi, E.; Servadei, F.; Romeo, S.; Grasso, E.; Sileri, P.; Giannelli, M.; Biancone, L.; Palmieri, G.; et al.
Abstract Aim First‐degree relatives (FDRs) of patients with colorectal cancer (CRC) have an increased CRC risk. Few studies have addressed if adenoma and advanced adenoma risk is increased among individuals, 40–49 years of age, with a family history of CRC. Therefore, the aim of the study was to define the prevalence and location of adenoma, advanced adenoma and CRC, according to age, in asymptomatic individuals with a family history of CRC. Method Retrospective study of asymptomatic FDRs, 40 to ≥70 years of age undergoing first screening colonoscopy over a 3‐year period, of CRC patients. Results Among 464 individuals studied, the prevalence of adenoma and advanced adenoma was 18.1% and 6.4%, respectively. According to age intervals, the prevalences of adenoma and advanced adenoma were 14% and 3.5%, respectively, in subjects 40–49 years of age; 14.4% and 6.3%, respectively, in subjects 50–59 years of age; 27% and 8%, respectively, in subjects 60–69 years of age; and 25% and 14%, respectively, in subjects ≥70 years of age; no significant difference was found among the four groups. No difference in lesion location was found, with similar numbers of preneoplastic lesions being present in the right colon and the left colon. CRC was diagnosed in three (0.64%) subjects, one of whom was in the 40–49 years age group. Conclusion In our population of FDRs of CRC patients, 40–49 years of age, the prevalences of adenoma and advanced adenoma were similar to those observed in older subjects with the same CRC risk. Our data support the current indication to perform screening colonoscopy earlier than 45 years of age in subjects at high CRC risk.